HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PENGGUNAAN HELM SNI PADA MAHASISWA KESEHATAN MASYARAKAT UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI TAHUN 2022 - RIZKI RAHMAWATI LESTARI; ETRI GUSTIANA (Universitas Pahlawan Tuanku Tambusai, 2022)
According to WHO, there were approximately 37,438 accidents that caused death, 70% of which were 2-wheeled motorized vehicles, 4-wheeled motorized vehicles accounted for 7% of all accidents in Indonesia. The Relationship of Knowledge and Attitude with the Use of SNI Helmets on Public Health Students at the Tuanku Tambusai University in 2022. The use of helmets according to the Indonesian National Standard (SNI) is the use of head protection from impact materials with foam, glass and helmet shell conditions that have met the safety requirements with embossed letter logo that reads SNI. The design of this study was an analytic survey with a cross sectional design. This research was conducted on 10-12 June 2022. The sample in this study amounted to 100 students using a total sampling technique. The data collection tool uses a questionnaire. Analysis of the data used in this study is a questionnaire. The results showed that there was a relationship between knowledge and the use of SNI helmets with a p value of 0.004 (<0.05) and there was a relationship between attitudes and the use of SNI helmets with a p value of 0.001 (<0.05). For students of the Hero University Tuanku Tambusai to be able to use a helmet in accordance with SNI standards so that safety can be maintained in order to avoid accidents.